Conversation with Saint Benedict : The Rule in Today's World - Kardong, Terrence (Book collections on Project MUSE., 2012)
The Rule of Saint Benedict meets contemporary culture; the connection points and the sticking points between the two are the focus of Conversation with Saint Benedict. Renowned Benedictine scholar Terrence Kardong considers various aspects of modern culture that he considers worrisome and the light that Benedict's Rule might shed on them for Christians today. He also takes up specific aspects of the Rule itself that he finds difficult to deal with. This book, then, offers a rich interplay that does not shrink from recognizing both strengths and weaknesses in modern culture as well as in Benedict's own ideas. Among the many topics that Kardong tackles are: laughter and tears; security; work; economics; monastic garb; cell phones; zeal; hierarchy; channel surfing.